2002
DOI: 10.1093/hmg/11.8.873
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of cone-rod homeobox (CRX) mutations associated with retinal dystrophy

Abstract: Mutations in the photoreceptor transcription factor cone-rod homeobox (CRX) have been identified in patients with several forms of retinal degenerative disease. To investigate the mechanisms by which these mutations cause photoreceptor degeneration, CRX constructs representing eleven known mutations, as well as a set of C-terminal deletions, were generated and tested for their ability to activate a rhodopsin-luciferase reporter in a transient cell transfection assay. To further define functional domains, sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
96
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 31 publications
(41 reference statements)
8
96
0
Order By: Relevance
“…The p.G255fs mutation in Crx Rip mice (as in several dominant LCA patients) removes the C-terminal Otx-like domain of CRX and instead adds 133 unrelated residues. As the truncated CRX 1-254 protein retains DNA binding and transactivation properties consistent with a previous study of CRX functional domains (49), the addition of unrelated residues in CRX Rip protein must interfere with the function of CRX WT and OTX2 proteins (as discussed earlier). As two dominant LCA-causing mutations examined here mimic the Crx Rip/+ phenotype, our studies provide a plausible molecular mechanism for congenital blindness in dominant CRX-LCA.…”
Section: Discussionsupporting
confidence: 77%
“…The p.G255fs mutation in Crx Rip mice (as in several dominant LCA patients) removes the C-terminal Otx-like domain of CRX and instead adds 133 unrelated residues. As the truncated CRX 1-254 protein retains DNA binding and transactivation properties consistent with a previous study of CRX functional domains (49), the addition of unrelated residues in CRX Rip protein must interfere with the function of CRX WT and OTX2 proteins (as discussed earlier). As two dominant LCA-causing mutations examined here mimic the Crx Rip/+ phenotype, our studies provide a plausible molecular mechanism for congenital blindness in dominant CRX-LCA.…”
Section: Discussionsupporting
confidence: 77%
“…Biochemical analysis has indicated that these factors are present at the promoters of rod-specific genes in vivo and directly activate expression of rod-specific genes (1,8,9). Mutation of rod-enriched transcription factors in humans can lead to rod photoreceptor dystrophy (10,11). Failure to express normal levels of rodspecific genes thus results in rod photoreceptor degeneration, and correction of this defect may have considerable value in treating inherited blindness.…”
mentioning
confidence: 99%
“…Mutations of the HD that increase the activity are unusual, but two reported examples are the CRX homeobox gene mutation E80A 45 and the NLR mutation S50T. 46 CRX is a transcription factor that is expressed in the rod and cone photoreceptors of the retina.…”
Section: Discussionmentioning
confidence: 99%